2017
DOI: 10.1590/0100-5405/2208
|View full text |Cite
|
Sign up to set email alerts
|

Alternative control to black spot disease in papaya genotypes

Abstract: To find control forms alternative to fungicides, this study aimed to evaluate the effect of products with potential to control black spot (Asperisporium caricae) in different papaya genotypes. Installed in a greenhouse, the experiment was conducted in randomized blocks (RB) with factorial arrangement 5x6, three replicates, and spraying of four products (Bion®, Bordeaux mixture, Ecolife®, and Bordasul®) in six papaya genotypes (‘Sunrise Solo PT’, ‘STZ 03’, ‘Golden’, ‘Tailândia’, ‘Maradol’ and ‘UENF-CALIMAN 01’)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Field experimentation with papaya has been carried out quite frequently in order to implement new technologies for the crop Santos et al, 2017) and to evaluate plant productivity (Oliveira et al, 2014;Dantas et al, 2015;Luz et al, 2015) and disease resistance (Poltronieri et al, 2017) of new genotypes. In experiments carried out to evaluate the productivity of new genotypes, Oliveira et al (2014) Dantas et al (2015) used 6 plants per plot and Luz et al (2015) 10 plants per plot, both with 4 replications in a randomized block design.…”
Section: Introductionmentioning
confidence: 99%
“…Field experimentation with papaya has been carried out quite frequently in order to implement new technologies for the crop Santos et al, 2017) and to evaluate plant productivity (Oliveira et al, 2014;Dantas et al, 2015;Luz et al, 2015) and disease resistance (Poltronieri et al, 2017) of new genotypes. In experiments carried out to evaluate the productivity of new genotypes, Oliveira et al (2014) Dantas et al (2015) used 6 plants per plot and Luz et al (2015) 10 plants per plot, both with 4 replications in a randomized block design.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the problems caused by fungicides in papaya crops, it is necessary to adopt alternative control strategies. Among them are the use of resistance-inducing products (Oliveira & Nishijima 2014, Santos et al 2017 and genetic resistance for the selection of resistant genotypes (Vivas et al 2012and 2015a, Poltronieri et al 2017. In spite of the efforts employed in the development of control methods against the black spot disease of papaya, no product is known to induce resistance in the plant, and neither there are cultivars resistant to the disease.…”
Section: Palavras-chavementioning
confidence: 99%
“…According to Martelleto et al (2009), the difficulty in controlling the papaya black spot is most evident in the organic production system due to few research results and to restriction on conventional fungicide use. To contribute to the alternative control for this disease, the application of phosphite, foliar fertilizers, and resistance inductors has been studied (Pratissoli et al, 2007;Oliveira and Nishijima, 2014;Santos et al, 2017). Oliveira and Nishijima (2014) concluded that the acibenzolar-S-methyl product induces partial resistance to the papaya against black spot; thus, it may be an option for the control of the disease.…”
Section: Introductionmentioning
confidence: 99%